One big happy family : 18 writers talk about polyamory, open adoption, mixed marriage, househusbandry, single motherhood, and other realities of truly modern love - Walker, Rebecca, 1969 Nov. 17- (New York : Riverhead Books, 2009)
'Edited by bestselling author Rebecca Walker, this anthology invites us to step into the center of a range of different domestic arrangements and take a good look around. From gay adoption to absentee fathers, from open marriages to green-card marriages, the reality of the American household has altered dramatically over the last three decades. With changing values and expectations, fluid gender roles, and a shifting economy, along with increase in infertility, adoption, and the incidence of mixed-race couples, people across the country are redefining the standard arrangement of family life. In a collection of eighteen honest, personal, and deeply affecting essays from an array of writers, One Big Happy Family offers a fresh look at how contemporary families are adapting to this altering reality' ... from Publisher's Description.
Keywords: Families -- United States; Social values -- United States